2011
DOI: 10.1021/jp1110295
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurement of Reaction Volume and Calculation of pH of Weak Acid Buffer Solutions Under High Pressure

Abstract: Direct measurements of reaction volume, so far, have been limited to atmospheric pressure. This study describes a method for in situ reaction volume measurements under pressure using a variable volume piezometer. Reaction volumes for protonic ionization of weak acid buffering agents (MES, citric acid, sulfanilic acid, and phosphoric acid) were measured in situ under pressure up to 400 MPa at 25 °C. The methodology involved initial separation of buffering agents within the piezometer using gelatin capsules. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Briefly, both pressure and temperature can lead to changes in p K a values of buffers and their respective acid dissociation equilibria. Acid–base equilibria can be shifted toward positive/negative Δ V (difference in the partial molar volumes of the neutral and the ionized species in equilibrium), according to Le Chatelier’s principle. While Δ V ∼ 0 mL/mol leads to pressure independence of pH, for some buffers, Δ V values can be significant (∼− 5 to −20 mL/mol) . However, the choice of buffers in high-pressure studies can be quite limited as even with some common examples (e.g., MES, TRIS, and imidazole) that have been reported to be quite resistant to pressure changes on p K a values , have an increase of pH of ca.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Briefly, both pressure and temperature can lead to changes in p K a values of buffers and their respective acid dissociation equilibria. Acid–base equilibria can be shifted toward positive/negative Δ V (difference in the partial molar volumes of the neutral and the ionized species in equilibrium), according to Le Chatelier’s principle. While Δ V ∼ 0 mL/mol leads to pressure independence of pH, for some buffers, Δ V values can be significant (∼− 5 to −20 mL/mol) . However, the choice of buffers in high-pressure studies can be quite limited as even with some common examples (e.g., MES, TRIS, and imidazole) that have been reported to be quite resistant to pressure changes on p K a values , have an increase of pH of ca.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Pressure‐induced transient pH shift has been reported in the literature. For example, Min (2008) reported that citric (pH 4.55, 570 mM) and phosphoric acids (pH 6.90, 58 mM) when treated under pressure (400 MPa at 25 °C) transiently shifted their pH towards acidic side by 0.57 and 1.24 pH units, respectively. Upon depressurization, pH values returned close to initial values.…”
Section: Resultsmentioning
confidence: 99%
“…This setup enabled the measurement of density and compressibility of various foods (Min and others ). Using the same sensor, and a further modification in the experimental protocol enabled Min and others () to determine the reaction volume of various weak acid buffer solutions under high pressure. The data were found to agree with chemical equilibrium data from the literature (El'yanov and Hamann ), up to a pressure of about 100 MPa—thereafter a divergence was observed.…”
Section: High‐pressure Processingmentioning
confidence: 99%
“…In this situation, the use of in‐situ monitoring can play a large role in helping elucidate the behavior of microorganisms or even chemical constituents during each of the process phases. Given the demonstrated nonuniformities in pressure distribution (Hartmann and others ), and the inadequacy (Min and others ) of existing theories in predicting chemical equilibria and reaction volumes, pressure and chemical sensors may become indispensable to future safety assurance during high‐pressure processing, much in the same manner that temperature sensing remains critical to thermal processing.…”
Section: High‐pressure Processingmentioning
confidence: 99%